Which Irish men and women immigrated to the United States during the Great Famine migration of 1846–54?. Issue 156 (18th December 2015) - Anbinder, Tyler; McCaffrey, Hope
Abstract: Despite the extensive scholarly literature on both the Great Famine in Ireland and the Famine immigration to the United States, little is known about precisely which Irish men and women emigrated from Ireland in the Famine era. This article makes use of a new dataset comprised of 18, 000 Famine-era emigrants (2 per cent of the total) who landed at the port of New York from 1846 to 1854 and whose ship manifests list their Irish county of origin. The data is used to estimate the number of emigrants from each county in Ireland who arrived in New York during the Famine era. Because three-quarters of all Irish immigrants intending to settle in the United States took ships to New York, this dataset provides the best means available for estimating the origins of the United States's Famine immigrants. The authors find that while the largest number of Irish immigrants came from some of Ireland's most populous counties, such as Cork, Galway, and Tipperary, surprisingly large numbers also originated in Counties Cavan, Meath, Dublin, and Queen's County, places not usually associated with the highest levels of emigration. The data also indicates that the overall level of emigration in the Famine years was significantly higher than scholars have previously understood.